2021
DOI: 10.1021/acs.energyfuels.1c02060
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Influencing Factors on the Kinetics Characteristics of Carbon Dioxide Hydrates in High Pressure Flow Systems

Abstract: Exploring the kinetics and flow characteristics of carbon dioxide hydrate slurry plays a critical role in the effective application of carbon capture technology by hydrate method and maintenance of the flow assurance. In order to better understand the formation and blockage process of carbon dioxide hydrate in the pipeline transportation system, a high-pressure flow experimental loop with a visible window was designed to study the formation process of carbon dioxide (CO2) hydrate and growth kinetics in a pure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Thus far, the hydrate high-pressure flow loop devices are one of the most effective methods to truly simulate the multiphase flow state in the actual pipeline. It usually includes a gas injection and liquid injection system, cool system, data acquisition system, test pipe section, etc . The schematic diagram of the hydrate loop device is shown in Figure .…”
Section: Technology and Equipment For Hydrate Formation And Depositio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, the hydrate high-pressure flow loop devices are one of the most effective methods to truly simulate the multiphase flow state in the actual pipeline. It usually includes a gas injection and liquid injection system, cool system, data acquisition system, test pipe section, etc . The schematic diagram of the hydrate loop device is shown in Figure .…”
Section: Technology and Equipment For Hydrate Formation And Depositio...mentioning
confidence: 99%
“…It usually includes a gas injection and liquid injection system, cool system, data acquisition system, test pipe section, etc. 44 The schematic diagram of the hydrate loop device is shown in Figure 3. The flow state parameters of the hydrate slurry in the loop can be accurately measured through the built-in sensor and imported to the computer through the data acquisition system.…”
Section: Technology and Equipment For Hydratementioning
confidence: 99%
“…The occurrence of a sudden pressure drop was considered to be the end of the induction time, and the time difference between the two points was taken as the hydrate induction time. This interpretation was slightly different from Zhang’s definition in which the point of a sudden drop in pressure and temperature rise was taken as the end of the induction time . After many experiments, it was not found that there was an obvious temperature surge in the loop, which may be because the nucleation rate of the CH 4 hydrate was slower than that of the CO 2 hydrate.…”
Section: Methodsmentioning
confidence: 79%
“…Therefore, the sensitivity analysis of the three influencing factors was carried out in this work using the standard regression coefficient method. The mathematical model is shown as follows: ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation